Keefektifan Konseling Kelompok Realita Dimensi Bernalar Kritis untuk Mengurangi Burnout Belajar Siswa SMP Pasca Pandemic - Hana Wilda Sholihah; Adi Atmoko; M. Ramli (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Academic burnout experienced by junior high school students post-pandemic hampers student motivation and academic achievement. Low motivation is very influential in increasing student achievement and willingness to learn. This study aims to test the effectiveness of group counseling with a critical reasoning dimension reality approach in reducing learning burnout of junior high school students. This study uses a quasi-experimental design with a quantitative approach. The subjects of the study were 10 students of grade VIII D SMPN 1 Kalitidu, who were divided into two groups: experimental and control. The sampling technique is purposive sampling. Data were collected using a learning burnout scale and analyzed with the Wilcoxon test. The results showed a significant decrease in the learning burnout rate of students after the intervention, with a value of Z = -2.023 and a significance of 0.043 (p < 0.05). Group counseling with a critical reasoning dimension reality approach is effective in reducing the learning burnout of junior high school students post-pandemic. This research opens up opportunities for the development of similar counseling programs in other schools to overcome learning burnout so that it car motivate student learning.